The Role of Price Fairness in Mediating the Effect of Product Quality and Service Quality on Repurchase Intention (A Study of Honda Car Customers in Bali) - I Putu Iwan Pramana PUTRA; Ni Putu Ayu Tika KURNIAWATI; Anak Agung Istri Krisna Gangga DEWI; Made Surya PRAMANA (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the role of price fairness as a mediating variable in the relationship between product quality, service quality, and repurchase intention among Honda car customers in Bali. The intense competition in the automotive industry in Bali requires companies to focus not only on product and service quality but also on effective pricing strategies to retain customers. Despite its importance, research on the role of price fairness as a mediator in this context is still limited. This study uses a quantitative approach with a survey method distributed to 160 respondents who are Honda car customers in Bali, selected using a purposive sampling technique. Primary data were collected through a questionnaire with a Likert scale and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results show that product quality does not have a significant direct effect on repurchase intention, and service quality has a positive and significant effect on repurchase intention. Furthermore, the findings confirm that price fairness significantly mediates the relationship between product quality and repurchase intention, as well as the relationship between service quality and repurchase intention. The output of this research is expected to provide strategic recommendations for Honda dealers in increasing customer retention through a better understanding of the role of price fairness.